2019
DOI: 10.1093/mnras/stz3356
|View full text |Cite
|
Sign up to set email alerts
|

Compact groups from semi-analytical models of galaxy formation – I. A comparative study of frequency and nature

Abstract: Compact groups (CGs) of galaxies are defined as isolated and dense galaxy systems that appear to be a unique site of multiple galaxy interactions. Semi-analytical models of galaxy formation (SAMs) are a prime tool to understand CGs. We investigate how the frequency and the three-dimensional nature of CGs depends on the SAM and its underlying cosmological parameters. Extracting 9 lightcones of galaxies from 5 different SAMs and selecting CGs as in observed samples, we find that the frequency and nature of CGs d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…As a result, the physical nature and the boundness of CGs have been debated for several decades. Both theoretical models (e.g., Mamon 1986;Tovmassian et al 2006) and simulation studies (e.g., Hernquist et al 1995;Díaz-Giménez & Mamon 2010;Hartsuiker & Ploeckinger 2020;Díaz-Giménez et al 2020) have suggested that CGs are mixture of virialized groups, chance alignments in filaments, and collapsing groups as bound substructures within clusters. An alternative scenario has also been proposed that the large groups are the birth-place of the embedded CGs (Diaferio et al 1994;Ramella et al 1994;Andernach & Coziol 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the physical nature and the boundness of CGs have been debated for several decades. Both theoretical models (e.g., Mamon 1986;Tovmassian et al 2006) and simulation studies (e.g., Hernquist et al 1995;Díaz-Giménez & Mamon 2010;Hartsuiker & Ploeckinger 2020;Díaz-Giménez et al 2020) have suggested that CGs are mixture of virialized groups, chance alignments in filaments, and collapsing groups as bound substructures within clusters. An alternative scenario has also been proposed that the large groups are the birth-place of the embedded CGs (Diaferio et al 1994;Ramella et al 1994;Andernach & Coziol 2005).…”
Section: Introductionmentioning
confidence: 99%
“…galaxies comprise 1% of all galaxies out to at least z ≈ 2 (Wiens et al 2019;Díaz-Giménez et al 2020), making this a fairly rare and noteworthy host environment. The large majority of observational CG studies are at low redshifts of z  0.2.…”
Section: The Host In the Context Of Compact Group Galaxies And Progen...mentioning
confidence: 99%